Formation of foreign competencies in students - Zhumanbekova Н. З.; Kabdusheva А.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
This article deals with the problem of forming one of the key communicative competences to master a foreign language, which is the main task of training qualified specialists in foreign philology. From the point of view the problem of forming one of the communicative competences can be derived from the foreign language, which is the basic task of the qualified specialists in the foreign philology. The development of future specialist competences in the foreign language the basic features of the description, the external and internal factors in practical terms are analyzed. Practical results are based on theoretical developments, observations, analyzes and experimental data processing in the process.